Blink index as a response predictor of blepharospasm to botulinum neurotoxin‐A treatment. Issue 11 (23rd September 2021) - Jang, Jeongkyeong; Lew, Helen
Abstract: Purpose: We investigated the blink profiles and blink index using ocular surface interferometer in the patients with blepharospasm (BSP) and identified points to consider predictive factor after BSP treatment. Methods: In total, 117 eyelids of 59 elderly patients and 20 eyelids of 10 age‐matched control group were studied. All BSP patients applied botulinum toxin‐A (BoNT‐A) injection for treatment of BSP. An ocular surface interferometer (LipiView; TearScience, Morrisville, NC, USA) was used to measure blink profile and blink index; total and incomplete blinks/20 s, and the partial blink ratio (PBR). Eyelid blink time (including lid closing time, closure time, lid opening time), interblink times (IBT), closing speeds (OS), and opening speeds (OS) were analyzed using 600 blinks recorded over 20 s. Results: Total blink rate was significantly higher in BSP patients compared to the age‐matched control group ( p  = .029) but other time‐related and speed‐related index including interpalpebral fissure, PBR, blink time, closure time (CT), interblink time, CS, and OS were not significantly different. In the responder of BSP patients, the average age was higher, CT was shorter, CS was faster than nonresponder (age; p  = .016, CT; p  < .001, CS; p  = .042). Conclusion: The blink index by analyzing the blink profile using ocular surface interferometer, and this blink index may be used as a predictive factor for evaluating the clinical response after BoNT‐A injection in blepharospasm patients. Abstract : This study provides us new understandings about the blink profile of blepharospasm patients using ocular surface interferometer. The blink index is a new predictive factor for the clinical response after botulinum ueurotoxin‐A treatment.